The branched-chain amino acid aminotransferase TaBCAT1 modulates amino acid metabolism and positively regulates wheat rust susceptibility. Issue 5 (5th February 2021) - Corredor-Moreno, Pilar; Minter, Francesca; Davey, Phoebe E; Wegel, Eva; Kular, Baldeep; Brett, Paul; Lewis, Clare M; Morgan, Yvie M L; Macías Pérez, Luis A; Korolev, Andrey V; Hill, Lionel; Saunders, Diane G O
Abstract : A branched-chain amino acid aminotransferase is essential for progression of wheat yellow and stem rust, two of the most economically damaging diseases of wheat worldwide. Abstract: Plant pathogens suppress defense responses to evade recognition and promote successful colonization. Although identifying the genes essential for pathogen ingress has traditionally relied on screening mutant populations, the post-genomic era provides an opportunity to develop novel approaches that accelerate identification. Here, RNA-seq analysis of 68 pathogen-infected bread wheat ( Triticum aestivum ) varieties, including three (Oakley, Solstice and Santiago) with variable levels of susceptibility, uncovered a branched-chain amino acid aminotransferase (termed TaBCAT1) as a positive regulator of wheat rust susceptibility. We show that TaBCAT1 is required for yellow and stem rust infection and likely functions in branched-chain amino acid (BCAA) metabolism, as TaBCAT1 disruption mutants had elevated BCAA levels. TaBCAT1 mutants also exhibited increased levels of salicylic acid (SA) and enhanced expression of associated defense genes, indicating that BCAA regulation, via TaBCAT1, has a key role in SA-dependent defense activation. We also identified an association between the levels of BCAAs and resistance to yellow rust infection in wheat. These findings provide insight into SA-mediated defense responses in wheat and highlight the role of BCAA metabolism in the defense response. Furthermore, TaBCAT1 could be manipulated to potentially provide resistance to two of the most economically damaging diseases of wheat worldwide.